Quantification of copolymer composition (methyl acrylate and itaconic acid) in polyacrylonitrile carbon-fiber precursors by FTIR-spectroscopy. Issue 2 (10th December 2015) - Loginova, Ekaterina V.; Mikheev, Ivan V.; Volkov, Dmitry S.; Proskurnin, Mikhail A.
Abstract : Conditions for simple and sensitive FTIR quantitative determination of acrylonitrile, methyl acrylate, and itaconic acid in their copolymer films used as precursor products in carbon-fiber manufacturing are proposed. Abstract : Conditions for simple and sensitive FTIR quantitative determination of acrylonitrile, methyl acrylate, and itaconic acid in their copolymer films used as precursor products in carbon-fiber manufacturing are proposed. The measurement mode is IR-spectrophotometry (transmission) with internal spectrum normalization using the peak of acrylonitrile at 2242 cm −1 as the main component and the determination of itaconic acid and methyl acrylate by their overlapping carbonyl peaks at 1740–1700 cm −1 . The calculations of comonomer concentrations were made using an external-standard method. The LOQs of itaconic acid and methyl acrylate are 0.5 and 2% w/w, respectively. The RSD of measurements is no higher than 7% rel. for methyl acrylate, 8% rel. for itaconic acid, and 1% rel. for acrylonitrile, which was shown by an example of analysis of PAN fiber samples with known concentrations of the components. The procedure was tested with several thermally unprocessed PAN precursor samples.